ANALISIS FAKTOR MUAT BUS TRANS METRO PEKANBARU KORIDOR TERMINAL BANDAR RAYA PAYUNG SEKAKI- KULIM - Alwinda, Yosi; Anggarini, Devita (FSTPT Indonesia, 2015)
Trans Metro Pekanbaru (TMP) is a public transportation that has been operating since 2009 in Pekanbaru. It has a function to reduce the problems related to public transport and traffic that appear because of the development of the city itself. During the time, the changing of passenger quantity, service quality and operation could happen anytime. Therefore, this research was done to find out the affectivity of TMP corridor II that serves the transportation from Terminal BRPS to Kulim with the load factor as the indicator.